Marketing of medicinal plants using landscape architectural design - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
Abstract Not many people realize the usefulness and curing properties of medicinal plants. Even though these plants have been used centuries ago, their importance has not been realized by the present generation. What is needed is some form of marketing techniques that combined landscape architecture design to generate and create awareness to the people on the contribution if these medicinal plants.